The birth of cool style narratives of the African diaspora - Tulloch, Carol (Bloomsbury Academic 2018, 2018)
It is broadly recognized that black style had a clear and profound influence on the history of dress in the twentieth century, with black culture and fashion having long been defined as cool . Yet despite this high profile, in-depth explorations of the culture and history of style and dress in the African diaspora are a relatively recent area of enquiry. The Birth of Cool asserts that cool is seen as an arbiter of presence, and relates how both iconic and ordinary black individuals and groups have marked out their lives through the styling of their bodies. Focusing on counter- and sub-cultural contexts, this book investigates the role of dress in the creation and assertion of black identity. From the gardenia corsage worn by Billie Holiday to the work-wear of female African-Jamaican market traders, through to the home-dressmaking of black Britons in the 1960s, and the meaning of a polo-neck jumper as depicted in a 1934 self-portrait by African-American artist Malvin Gray Johnson, this study looks at the ways in which the diaspora experience is expressed through self-image. Spanning the late nineteenth century to the modern day, the book draws on ready-made and homemade fashion, photographs, paintings and films, published and unpublished biographies and letters from Britain, Jamaica, South Africa, and the United States to consider how personal style statements reflect issues of racial and cultural difference. The Birth of Cool is a powerful exploration of how style and dress both initiate and confirm change, and the ways in which they expresses identity and resistance in black culture